The Effect of Corporate Social Responsibility Cost and Fi-nancial Ratios on Tax Avoidance Evidence from Large Market Capitalization Firms in Indonesia - Azzahra Putri Ariesta; Susi Sarumpaet (International Journal of Economics, Commerce, and Management, 2026)
This study aims to examine the effect of Corporate Social Responsibility (CSR) costs and financial characteristics on tax avoidance practices among publicly listed companies with the largest market capitalization in Indonesia. The study is motivated by Indonesia’s relatively low tax ratio compared to other emerging economies in the ASEAN region, which suggests the persistence of tax avoidance practices, particularly among large corporations. Grounded in legitimacy theory and agency theory, this research empirically investigates the influence of CSR costs, profitability, leverage, liquidity, activity ratio, growth ratio, and operating cash flow on tax avoidance. The research sample consists of 50 companies with the largest market capitalization listed on the Indonesia Stock Exchange over the 2020–2024 period, employing a census sampling method and unbalanced panel data. Secondary data were obtained from annual financial reports and analyzed using panel data regression techniques. Tax avoidance is measured using the Book-Tax Differences (BTD) approach, while model selection is determined through the Chow test, Hausman test, and Lagrange Multiplier test. The results indicate that, simultaneously, all independent variables have a significant effect on tax avoidance. Partially, the activity ratio has a negative effect on tax avoidance, whereas the growth ratio and operating cash flow have a positive effect on tax avoidance. Meanwhile, CSR costs, profitability, leverage, and liquidity do not show a significant effect. These findings suggest that asset utilization efficiency tends to restrain tax avoidance behavior, while corporate growth dynamics and strong operating cash flows encourage more aggressive tax management strategies. This study provides empirical evidence from an emerging market context and offers insights for tax authorities and regulators in designing more effective, risk-based tax supervision policies.